A Comparative Functional Analysis of Discourse Markers in the Native and the Non-Native English Newspaper Business Corpus - Ammara Riaz (Journal of Peace, Development and Communication, 2021)
The current study explores the functional nature of Discourse Markers (DMs) in the newspaper business corpus. DMs function as cohesive devices which, additionally, carry pragmatic and semantic meanings present in both the written and the spoken discourse. The focus of this study is to comparatively highlight the differences in the functions of DMs in the business discourse of the native and the non-native newspapers. The study has employed Fung’s (2003) multi-categorical comprehensive framework of DMs. The framework functionally divides DMs into interpersonal, cognitive, structural, and referential categories. These major categories have further been divided into many subcategories of DMs. Based on this comprehensive framework; the current study identifies different functional DMs and compares them for their quantitative and qualitative differences in use. For the analysis of this study, a corpus of one million words was collected from the native business newspapers (The Daily Mail and The Telegraph) and the non-native business newspapers (The Dawn, The Business Recorder, The Nation and Daily Times). Data analysis shows that the most frequently used functional categories of DMs among the native writers are referential and structural, while the least frequently used functional category is cognitive. On the other hand, non-native Pakistani writers make more use of functional DMs of referential, structural and cognitive categories, while the least frequently used functional category is interpersonal. This quantitative difference in the use of DMs makes the native business corpus more coherent and interactive than that of the non-native business corpus. It is expected that the findings of the study may help understand the differences of textuality in the native and the non-native newspaper corpus. It is also expected that the findings of the current study can assist curriculum developers and ESL instructors in developing better teaching materials for second language learners. Keywords: Discourse Markers, Business Discourse, Functional Categories of DMs